Factors affecting female consumers' acceptability on nail polish - Sun, Chen (Kansas State University, 2014)
The market of nail polish has been booming in recent years. Research on nail polish is scarce. A sensory lexicon for nail polish has been developed at Kansas State University, but how sensory factors affect female consumers’ acceptability of nail polish has not been examined. Also, other factors, such as price and usage characteristics that could affect consumers’ acceptability, are yet to be determined. A nail polish consumer study was conducted at Kansas State University to explore several sensory and non-sensory factors that could affect female consumers’ acceptability of nail polish. Eight nail polish samples, belonging to four categories, namely, regular (REG), gel (GEL), flake (FLK) and water-based (WAT), were evaluated by each of the 98 female consumers. The questionnaire consisted of three sections – application, observation and general usage questions. Results showed that consumers rated the samples similarly in both the application and observation sections. In general, consumers preferred the REG and the GEL samples more than the FLK and the WAT samples. Among all the sensory attributes, appearance attributes were the major attributes that affected consumers’ overall acceptability, while aroma had negligible impact on acceptability. Some sensory attributes like runny, shininess, opacity, spreadability, smoothness, coverage and wet-appearance were found to drive the consumer’s overall acceptability positively, while others such as pinhole, fatty-edges, blister, brushlines, pearl-like, flake-protrusion, glittery and initial-drag impacted their liking negatively. Four clusters of consumers were identified based on the consumers’ overall liking scores for both the application and observation sections. Considering all the factors that could affect consumers’ acceptability, sensory appeal, price, and conveniences of usage were the top factors picked by consumers. Age was also a factor that affected consumers’ acceptability for some of the samples. Consumers’ overall acceptability for these studied samples could guide a beauty store or a nail salon on building their selection on nail polishes. Consumers’ acceptability on different sensory attributes could help a nail polish company modify or improve their nail polish formula. The consumer cluster information could benefit a nail polish company on marketing a specific category of product and advertising to a specific group of consumers.
Keywords: Nail polish; Acceptability; Sensory study; Consumers; Preference mapping; Marketing; Food Science (0359); Marketing (0338)